A global ‘greening’ of coastal dunes: an integrated consequence of climate change? - Jackson, Derek W. T. (2019)
In the context of global climate change and sea-level rise, coastal dunes are often important elements in the coastal response to storm wave and storm surge impacts on coastal lowlands. Vegetation cover, in turn, has profound impacts on coastal dune morphology and storm-buffering function; it binds existing sediment, promotes fresh sediment accumulation and thereby increases dune volume and dune crest elevation where a sediment-plant interaction plays out with vegetation growth attempting to out-pace the vertical sediment accumulation. A global analysis shows that vegetation cover has increased substantially on multiple, geographically dispersed, coastal dune fields on all continents in the period 1984-2017. The observed 'greening' points to enhanced dune stability and storm buffering effects at a time when, paradoxically, coasts are being subjected to increased flood and erosion risk from rising sea levels and changing patterns of storminess. Causal attribution of biological trends to climate change is complicated, but we contend that the global scale 'greening' of coastal dunes is driven by a combination of changes to climate and atmospheric composition and reflects the cumulative effects of changes in temperature, precipitation, nutrient concentration and reduced windiness (global stilling). Global-scale increases in temperature, nutrients and precipitation (all of which are vegetation growth stimulants) and widespread reduction in windiness ("stilling") (which reduces sediment activity, promoting the spread of vegetation) coincide in time with the observed changes in vegetation cover. The observed changes in coastal dunefields enhance contemporary and near-future coastal resilience to climate change and may represent a previously unrecognised morphological feedback mediated by climate change.